Analysis of the relocation of the Sakai Anak Dalam tribe to Madani housing in Lubuk Jering village, Air Hitam sub-district, Sarolangun regency - Sari Mustika; Rika Despica; Slamet Rinto (Edumaspul: Jurnal Pendidikan, 2025)
This research is based on the Relocation of Suku Anak Dalam (SAD) Residences in Madani Housing in Lubuk Jering Village, Air Hitam District, Sarolangun Regency. This research was conducted to analyze: 1) Characteristics of Suku Anak Dalam (SAD) in Lubuk Jering Village, Air Hitam District, 2) Inhibiting Factors for Relocation of Suku Anak Dalam (SAD) in Madani Housing in Lubuk Jering Village, Air Hitam District, 3) The Role of the Government towards Suku Anak Dalam (SAD) in Lubuk Jering Village. The type of research used is qualitative. This research was conducted in Lubuk Jering Village, Air Hitam District, Sarolangun Regency. Research informants used the Snowball Sampling technique, with Suku Anak Dalam (SAD) community leaders as key informants and Village Officials as supporting informants. Data collection and analysis were carried out using NVivo software version 15. The results of the study show: 1) The characteristics of Suku Anak Dalam (SAD) in Lubuk Jering Village are that the average livelihood is food gathering. The clothing of the Suku Anak Dalam (SAD) for men uses a loincloth (koteka) while women wear cloth (sandang). Most of the Suku Anak Dalam (SAD) have beliefs in spirits who speak Malay and kubu. 2) Factors inhibiting the relocation of the Suku Anak Dalam (SAD) in Lubuk Jering Village are influenced by the cultural tradition of melangun (a culture of leaving a residence temporarily after a family member dies), in addition to their dependence on the forest making it difficult for them to settle in one place. 3) The role of the government towards the Suku Anak Dalam (SAD) in Lubuk Jering Village provides free housing facilities and health insurance for the Suku Anak Dalam (SAD). However, these efforts have not been optimal because they are not accompanied by the provision of agricultural land. Even though the Suku Anak Dalam (SAD) community really hopes for agricultural land as their main source of livelihood.